An Investigation of Harpellales (Trichomycetes) in New York State Blackflies (Diptera: Simuliidae) - Labeyrie, E. S.; D. P. Molloy; Lichtwardt, R. W. (Journal of Invertebrate Pathology, 1996)
This research project investigates the distribution and prevalence of trichomycete fungi present in blackfly larvae and adults in the region of Cambridge, New York. In blackfly larvae, two genera of Harpellaceae,StachylinaandHarpella,were observed in midguts, and four genera of Legeriomycetaceae—Pennella, Genistellospora, Simuliomyces,andSmittium—in hindguts, with a total of seven species recorded. This is the first published report ofStachylinaspp. in blackflies. Field data indicated that sampling date, host species, and location were all important variables affecting trichomycete prevalence in larvae. We report the successful laboratory infection of blackfly larvae within vitroculturedSmittium simulii,and production ofH. melusinaeandG. homothallicatrichospores from cysts dissected from the ovaries of infected flies.
Keywords: fungi; Harpellales; ovarian cysts; Simuliidae; Trichomycetes